Recycling agricultural waste through organic formulations enhances crop growth, crop productivity, and soil health in triple crop system - Garg, Kamal; Dhar, Shiva; Kumar, Dilip; Sharma, V. K.; Reddy, Marthala Bhuvaneswar; Gupta, Gaurendra; Giri, Balendu Shekhar; Hashim, Mohammad; Rajawat, Mahendra Vikram Singh; Jaiswal, Durgesh Kumar; Awasthi, Mukesh Kumar; Azman, Elisa Azura; et al. (Elsevier B.V., 2025)
Recycling agricultural residues into organic formulations offers a sustainable strategy to reduce reliance on limited farmyard manure (FYM) resources and improve soil and crop performance. Anchored in the principles of sustainable nutrient recycling and agroecological intensification, present study evaluated effects of organic formulations prepared from agro-waste such as paddy husk ash (PHA) and potato peel compost (PPC) on crop growth, productivity, and soil health in triple crop rotation system. A two-year field experiment (2020–22) was executed at ICAR-IARI, New Delhi, using a randomized block design with seven nutrient management treatments. Crop growth, yields, soil health indicators, soil physical, chemical and biological properties were assessed. Among treatments, T4 (applied with 100% Recommended dose of nitrogen (RDN) through a PHA-based formulation) consistently achieved the highest yields: baby corn (7.42–7.53 t ha-1), kabuli gram (2.16–2.21 t ha-1), and cowpea (6.83–6.95 t ha-1), followed by T6 (100% RDN via a potato peel compost (PPC)-based formulation) and T2 (100% RDN through FYM). Soil under T4 showed substantial improvements in NH4+-N (11.3–13.3 mg kg-1) and NO3--N (20.6–21.9 mg kg-1), representing 68–91% and 111–144% increases over the control. Enzymatic activities, including dehydrogenase (39–41%) and alkaline phosphatase (33–37%), were also significantly enhanced. Additionally, microbial populations and microbial biomass carbon (239 mg kg-1) increased by 20–36% and 25%, respectively, compared with the control (T1). PHA- and PPC-based formulations demonstrated strong potential as effective substitutes for FYM alone, improving crop growth, yields, and enhancing soil health. Their use can promote sustainable nutrient recycling and soil health in regions with limited availability of conventional organic inputs.